2016
DOI: 10.1002/joc.4723
|View full text |Cite
|
Sign up to set email alerts
|

Historical trends in precipitation, temperature and drought in the Alabama–Coosa–Tallapoosa and Apalachicola–Chattahoochee–Flint river basins

Abstract: Using station data from the United States Historical Climatology Network, we preformed a running trend analysis of temperature, precipitation and drought in the Alabama–Coosa–Tallapoosa and Apalachicola–Chattahoochee–Flint river basins for the time period 1895–2012 on annual and monthly timescales. Our study found that long‐term precipitation and temperature trends were statistically detectible but relatively slight in the order of an increase at 3 mm per decade for precipitation and a decline of 0.02 °C per d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
1
3
1
Order By: Relevance
“…Frontiers in Ecology and 10 frontiersin.org most sites, and especially in winter, but in other seasons as well. This contrasts to other studies of temperature trends within other river basins in the region that found relatively static high temperatures (Maleski and Martinez, 2017). This contrast may be due to differences in the period of analysis in both scale (118 years versus 36 years) and the influence of more contemporary temperature data.…”
Section: Similarities and Differences In Trendscontrasting
confidence: 91%
See 1 more Smart Citation
“…Frontiers in Ecology and 10 frontiersin.org most sites, and especially in winter, but in other seasons as well. This contrasts to other studies of temperature trends within other river basins in the region that found relatively static high temperatures (Maleski and Martinez, 2017). This contrast may be due to differences in the period of analysis in both scale (118 years versus 36 years) and the influence of more contemporary temperature data.…”
Section: Similarities and Differences In Trendscontrasting
confidence: 91%
“…In general, precipitation has not significantly increased or decreased at annual or seasonal scales, suggesting that total rainfall amounts have been the same over the past 36 years. These results mirror similar studies that found precipitation to be relatively stable in the late 20th and early 21st Centuries (Ficklin et al, 2016;Maleski and Martinez, 2017). This is seen despite changes in global multi-annual climate patterns such as El Nino-Southern Oscillation that could result in wetter conditions in summer and fall in El Nino years and drier conditions in La Nina years (Ropelewski and Halpert, 1986;Clark II et al, 2014).…”
Section: Similarities and Differences In Trendssupporting
confidence: 88%
“…Additionally, overall precipitation in several watersheds that drain the Atlanta MSA has increased, albeit slightly (Maleski and Martinez 2016). There is also abundant evidence that increased urban development will alter both precipitation patterns (Changnon 1980;Changnon 2001;Changnon and Westcott 2002;Shepherd et al 2002;Ntelekos et al 2007;Bentley et al 2010;Haberlie et al 2015) and runoff characteristics (Leopold 1968;Graf 1977;Ferguson and Suckling 1990;Booth 1991;Changnon et al 1996;Zhang and Smith 2003;Villarini et al 2009;Yang et al 2013) which can expand floods of a given return period.…”
Section: Regional Resultsmentioning
confidence: 99%
“…block bootstrapping Mann-Kendall test(Kundzewicz & Robson 2000;Önöz & Bayazit 2012). These upper triangle graphs are partly analogous to those illustrated byObregón et al (2014);Maleski & Martinez (2017).In addition, the 1:1 line and its parallel ones indicate estimated trends of 30 years and longer periods with different beginning and ending times. The most bottom-left and upper-right grid cells stand for the earliest and latest 30 years, respectively,…”
mentioning
confidence: 78%
“…Over the last few decades, there have been various salient case studies of long-term trends in temperature, precipitation, and extreme events. For example, Ngo-Duc ( 2014 Maleski & Martinez (2017).…”
Section: Introductionmentioning
confidence: 99%